Real-World Evidence on the Effectiveness of AlphaTM – Liv Sugar Free in Managing Sluggish Liver Functions And Fatty Liver: A Post-Marketing Physician Survey (Advancements in Homeopathic Research, 2025)
Introduction: Liver dysfunction, including sluggish  liver and fatty liver disease, poses a growing global  health challenge, exacerbated by lifestyle factors and  hepatotoxic exposures. Conventional therapies offer  relief but are often limited by side effects, prompting  increased interest in complementary hepatoprotective  remedies. Alpha™-Liv Sugar Free Liver Tonic- a  multi-ingredient homeopathic tonic, is known for its  efficacy in management of liver diseases in diabetic  patients. This study aimed to evaluate the real world effectiveness and safety of Alpha™-Liv Sugar  Free Liver Tonic in managing functional hepatic  disturbances. Methods & Methods: A post-marketing survey was  conducted using a structured Google Form distributed  to physicians across India. Data was collected on  speed of action, clinical effectiveness, and adverse  effects based on physicians’ experience with Alpha™- Liv Sugar Free Liver Tonic. Responses from 80  prescribing doctors were analyzed using descriptive  statistics. Results: Of the respondents, 90% rated Alpha™-Liv  Sugar Free Liver Tonic effectiveness between 4 and  5, indicating high therapeutic benefit. Over 93.75%  observed symptomatic improvement within a week.  A favorable safety profile was reported by 98.75% of  physicians, with negligible adverse effects noted. Conclusion: Alpha™-Liv Sugar Free Liver Tonic  demonstrates strong clinical acceptance for its  effectiveness and rapid action in liver dysfunction  management. Its multi-targeted homeopathic  formulation and high tolerability make it a promising  option in integrative hepatology.
Keywords: Alpha™-Liv Sugar Free; liver tonic; hepatoprotective; fatty liver; sluggish liver; real world evidence; post-marketing survey; homeopathic formulation; integrative medicine